A review of the hyperiidean amphipod superfamily Vibilioidea Bowman and Gruner, 1973 (Crustacea: Amphipoda: Hyperiidea) - Zeidler, Wolfgang (Zootaxa, 2003)
A taxonomic review of the hyperiidean superfamily Vibilioidea is presented, based on material held by most of the major museums in the world. Three families are recognised as belonging to the superfamily. It is proposed to remove Cyllopus from the family Vibiliidae, based on the positioning of the antennae and other minor characters inconsistent with other members of the family, and to resurrect the family Cyllopodidae Bovallius, 1887 to accommodate it. Two species of Cyllopus are recognised in this review. The family Vibiliidae is restricted to two genera; Vibilia and Vibilioides. Seventeen species of Vibilia are recognised in this review, including two described as new to science. Ten nominal species of Vibilia, considered nomen dubia, are discussed. Vibilioides is considered to be monospecific. The family Paraphronimidae is currently monogeneric with two species. A key to all species is provided.